Pathological role of activated mTOR in CXCR3+ memory B cells of rheumatoid arthritis. (9th March 2021) - Iwata, Shigeru; Zhang, Mingzeng; Hajime, Maiko; Ohkubo, Naoaki; Sonomoto, Koshiro; Torimoto, Keiichi; Kitanaga, Yukihiro; Trimova, Gulzhan; Todoroki, Yasuyuki; Miyata, Hiroko; Ueno, Masanobu; Nagayasu, Atsushi; et al.
Abstract: Objectives: B cells play an important pathological role in RA. In this study, we investigated the role of metabolic regulator mTOR in B cells and its relevance to the pathology of RA. Methods: Peripheral blood mononuclear cells were isolated from 31 normal subjects and 86 RA patients and the gated B cells were assessed for mTOR phosphorylation and chemokine receptor expression. In vitro studies on peripheral blood B cells isolated from the control and RA patients investigated the molecular mechanisms. Results: Higher concentrations of CXCL10 (CXCR3 ligands) and lower percentages of CXCR3 + memory B cells were present in the peripheral blood of RA patients relative to the control. RA patients with high CXCL10 concentrations had smaller percentage of CXCR3 + memory B cells and high disease activity. One-year treatment with TNF inhibitors increased the percentage of CXCR3 + memory B cells and reduced serum CXCL10 concentrations. mTOR phosphorylation in B cells was further enhanced in RA patients, compared with the control, and was selectively enhanced in CXCR3 + memory B cells. mTOR phosphorylation in CXCR3 + memory B cells correlated with disease activity. In vitro, mTOR phosphorylation in B cells enhanced IL-6 production and increased RANKL expression. Conclusion: mTOR activation in CXCR3 + memory B cells of RA patients is associated with disease activity, mediated through IL-6 production and RANKL expression. The obtained results also suggest that TNF inhibitors mediate an impact on the association between CXCL10 and mTOR activated CXCR3 + memory B cells.